Surgical Treatment of Double-Layered Lateral Meniscus - Masataka Ota; Hiroshi Takagi; Shin Kato; Fumiyoshi Kawashima; Koji Kanzaki (Case Reports in Orthopedics)
This is a rare case of a patient with a double-layered lateral meniscus, undergoing surgical treatment. A 17-year-old woman who was a member of a volleyball club had a two-year history of right knee pain with episodes of locking, although she had no history of trauma. She was referred to our hospital because her condition did not improve after conservative treatment. On presentation to the hospital, she had full range of motion in the right knee. McMurray’s test revealed no clicks; however, it produced pain in the lateral part. Plain radiography revealed no abnormal findings, whereas magnetic resonance imaging showed high signal in the posterior segment of the lateral meniscus and an increase in its volume. Arthroscopic findings showed an accessory meniscus with a flat surface overlying a normal-sized lateral meniscus. It was firmly connected to the posterior root and middle segment of the lower normal meniscus. The accessory meniscus was markedly mobile as revealed by probing. The patient was diagnosed with double-layered lateral meniscus and underwent resection of the accessory meniscus. Postoperatively, she initiated strengthening of muscles and range of motion training without weight-bearing restrictions. Two months postoperatively, she had completely recovered and participated in volleyball practices. In the last follow-up at 18 months, she had no restrictions in daily or sports activities.